Quantitative and phylogenetic study of the Deep Sea Archaeal Group in sediments of the Arctic mid-ocean spreading ridge - Steffen L. Jørgensen (Department of Biology, Centre for Geobiology, University of Bergen); Ingunn H. Thorseth (Department of Earth Science, Centre for Geobiology, University of Bergen); Rolf B. Pedersen (Department of Earth Science, Centre for Geobiology, University of Bergen); Tamara Baumberger (Department of Earth Science, Centre for Geobiology, University of Bergen); Christa Schleper (Department of Ecogenomics and Systems Biology, Faculty of Life Sciences, University of Vienna) (Frontiers in Microbiology, 2013)
The abstract is available here: https://uscholar.univie.ac.at/o:502505 The abstract is available here: https://uscholar.univie.ac.at/o:502505